2019
DOI: 10.1186/s12884-019-2608-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for placenta accreta spectrum: findings from the Japan environment and Children’s study

Abstract: BackgroundPlacenta accreta spectrum (PAS) is a life-threating complication in the field of obstetrics. Sometimes we face with unexpected PAS cases which is potentially higher maternal mortality and morbidity compared with expected cases. The present study was conducted to examine the prevalence of PAS and to elucidate its risk factors using a large Japanese birth cohort study.MethodsWe reviewed the results of a nationwide prospective birth cohort study in Japan, and identified 90,554 participants treated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 28 publications
4
82
0
2
Order By: Relevance
“…Further investigation is necessary since GnRHa therapy is a widely used medication both in IVF protocols, in treatment of endometriosis, and more recently in patients with adenomyosis. Pregnancies conceived after IVF do have an increased risk for subsequent placenta accreta [ 15 , 16 ]. These studies did not compare GnRH agonist vs GnRH antagonist protocols, but that could be a potential area of study in the future [ 15 , 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation is necessary since GnRHa therapy is a widely used medication both in IVF protocols, in treatment of endometriosis, and more recently in patients with adenomyosis. Pregnancies conceived after IVF do have an increased risk for subsequent placenta accreta [ 15 , 16 ]. These studies did not compare GnRH agonist vs GnRH antagonist protocols, but that could be a potential area of study in the future [ 15 , 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancies conceived after IVF do have an increased risk for subsequent placenta accreta [ 15 , 16 ]. These studies did not compare GnRH agonist vs GnRH antagonist protocols, but that could be a potential area of study in the future [ 15 , 16 , 21 , 22 ]. Although larger studies have shown that endometriosis is associated with increased risk for placenta accreta, smaller studies did not find an association as it was a rare outcome [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kyozuka et al . 9) recently reported that undergoing CS two or more times, smoking during pregnancy, becoming pregnant through assisted reproductive technology, and uterine anomalies are all independent risk factors for unexpected PAS in the absence of placenta previa. Therefore, it is crucial to maintain a high index of suspicion for PAS during the antenatal period in patients with these risk factors, even without placenta previa.…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factors of PAS are previous C/S and intrauterine operation [10][11][12]. Other risk factors included placenta previa, multiparity, maternal age, any previous uterine surgery, surgical abortion, radiation, endometrial ablation, in vitro fertilization (IVF), chemotherapy, and adenomyosis [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of C/S in the United States is 32-33% and placentas accreta is equal to 1/540-1/2500 of total deliveries [1]. It has increased since the early 1900s and according to one meta-analysis , overall prevalence of PAS is 0.17% (range from 0.01 -1.1% ) [12,13]. The rate of PAS in women with placenta previa without previous C/S is 3% and with 1, 2, 3 times C/S reaches 11%, 40%, and 60%, respectively [1].…”
Section: Introductionmentioning
confidence: 99%